Evaluation of Paulownia-based Tree-crop Intercropping Systems under Rainfed Conditions in Doon Valley - Singh, Charan; Dhyani, S. K.; Dhiman, R. C.; Sharma, K. K.; Kumar, Nirmal (Indian Forester, 2009)
In agroforestry practices generally tree has more pronounced effect on crop growth and yield with increase in its canopy cover. But in the present investigations results indicated that there was no significant (P<0.05) effect of trees on crop. The survival, growth, biomass production and leaf nutrient content of Paulownia were significantly higher as compared with poplar under the agroforestry situation. Similarly, nitrogen (3.02 %) and protein (18.8 %) contents in tree leaves were also highest with the Paulownia clone-GP. Although, the size of the leaves and canopy of Paulownia is larger than the poplars even then influence on yield and yield attributing characters was lesser as the highest yield was recorded under Paulownia only. It is evident from the results that Paulownia and Poplar clones do not have any significant effect on almost all the growth and yield parameters of wheat and maize crops grown in association with trees. The grain yield for wheat crop has a very little difference but maize does not have the difference under the different clones. It indicates the best compatibility of the crops with Paulownia and poplar. it is inferred that over all Paulownia clone-GP out performed all the clones of Paulownia fortunei and Populus deltoides. Thus, the tree has great potential under agroforestry situations in similar agro-climatic conditions of India.